Network of public equity funds and investment performance in South Korea - Yongwon Kim; Inwook Song; Young Kyu Park (Journal of Derivatives and Quantitative Studies: Seonmul yeon'gu (JDQS), 2024)
Using overlapped portfolio data on public equity funds in Korea, the authors construct several types of fund-stock weighted bipartite networks and measure fund network centrality. The authors also examine the relationship between network centrality and fund investment performance. The authors' results are three-fold. First, the authors find that the fund centrality of the network in which funds and stocks are connected based on the most active investing behavior positively affects the fund performance. Second, the funds with a high centrality level based on the same network generate higher returns by holding stocks with high value uncertainty. Third, the authors find that fund centrality is not associated with herd behavior. Based on these results, the authors argue that fund centrality is a proxy of information advantage and skill of fund managers. The authors' paper shows that network analysis could be a new way to identify funds with better performance and measure the skill and information advantage to construct an optimal portfolio.
Keywords: 330; Centrality; Excess return; Herd behavior; Network analysis; Value uncertainty